Hijas del Muntu.
1 online resource
Keywords: "Stories of Latin American Women of African Heritage: Daughters of Muntu highlights the significant contributions of women in the African diaspora to the Americas. A translation to English of the highly influential Hijas del Muntu, the chapters of this edited collection illuminate life experiences and examine narrative threads and traces of identity whose common theme is the history of struggle for equal rights and participation in society. The diverse women in these stories come from all walks of life, from to singers and poets to favela leaders and mainstream politicians. Their stories are told through interviews, personal accounts, and traditional academic biography. Stories of Latin American Women of African Heritage: Daughters of Muntu will be a valuable resource to those studying Latin American Studies, Gender Studies, and Race Studies among other disciplines"-- Provided by publisher.